Parrotfish grazing ability: interspecific differences in relation to jaw-lever mechanics and relative weight of adductor mandibulae on an Okinawan coral reef - Atsushi Nanami (PeerJ, 2016)
Parrotfishes (family Labridae: Scarini) are regarded to have important roles for maintaining the ecosystem balance in coral reefs due to their removal of organic matter and calcic substrates by grazing. The purpose of the present study was to clarify the interspecific differences in grazing ability of five parrotfish species (Chlorurus sordidus, C. bowersi, Scarus rivulatus, S. niger and S. forsteni) in relation to interspecific differences in jaw-lever mechanics and the relative weight of the adductor mandibulae (muscles operating jaw closing). The grazing ability was calculated by using stomach contents (CaCO3 weight/organic matter weight) defined as the grazing ability index (GAI). There were significant interspecific differences in GAI (C. sordidus = C. bowersi > S. rivulatus > S. niger = S. forsteni). Teeth of C. sordidus and C. bowersi were protrusive-shape whereas teeth of S. rivulatus, S. niger and S. forsteni were flat-shape. C. sordidus and C. bowersihave jaw-lever mechanics producing a greater biting force and have a larger weight of adductor mandibulae. S. rivulatus has jaw-lever mechanics producing a greater biting force but a smaller weight of adductor mandibulae that produce an intermediate biting force. In contrast, S. niger and S. forsteni have jaw-lever mechanics producing a lesser biting force and have a smaller weight of adductor mandibulae. Feeding rates and foray size of S. rivulatus, S. niger and S. forsteni were greater than C. sordidus and C. bowersi. The degree in bioerosion (GAI × feeding rate) was the largest for S. rivulatusand the smallest for S. forsteni. The degree in bioerosion for C. sordidus was larger than S. niger whereas relatively equal between C. bowersi and S. niger. These results suggest that interspecific difference in GAI was explained by interspecific differences in teeth shape, jaw-lever mechanics and relative weight of adductor mandibulae. The interspecific difference in the degree of bioerosion suggests the importance of various size of parrotfishes with diverse feeding modes to maintain healthy coral reef ecosystems.